Thin Layer Drying of Stinging Nettle (Urtica Dioica) Leaves in Cabinet Dryer and Selection of Appropriate Drying Model - Dangol, Abina; Dhungel, Abhitosh; Dhakal, Santosh (Journal of Food Science and Technology Nepal, 2024)
The present study was conducted to examine the drying kinetics of stinging nettle (Urtica dioica) leaves, both pretreated and untreated, in a cabinet dryer. The leaves were blanched at 90°C for one minute before drying at temperatures of 50, 55, or 60°C. The control group involved drying the leaves without any blanching. The drying of stinging nettle leaves followed only a falling rate period. Graphical and statistical analysis of the result showed that Midilli and Verma models were the best-fitted models for cabinet drying of stinging nettle leaves. The time required to dry unblanched leaves from an initial moisture content of ~8.54±0.86% db to a final moisture content of ~1.11±0.01% db was 90, 75, and 60 minutes at 50, 55, and 60℃, respectively. Similarly, the time required to dry blanched leaves was 75, 60, and 45 minutes at 50, 55, and 60°C respectively. The rehydration ratio of stinging nettle varied from 3.08±0.09 to 4.26±0.01 for unblanched and 3.40±0.15 to 4.52±0.07 for blanched product dried at 50-60℃. The Deff of leaves was increased from 1.2-2.5×10-12m2/s for unblanched leaves and 2-3.1×10-12m2/s for blanched leaves as the drying temperature increased from 50-60℃. The activation energy was estimated to be 65.2 kJ/mol for unblanched leaves and 38.9 kJ/mol for blanched leaves. Drying (at 55℃) retained 43% and 31% of total chlorophyll and β-carotene respectively while drying with blanching retained 38% and 57% total chlorophyll and β-carotene respectively.